IMPLEMENTASI FUNGSI MANAJEMEN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA PADA KEPEMIMPINAN NABI MUHAMMAD SAW - Juliadarma, Minggusta (STKIP Pesisir Selatan, 2023)
The leadership of Prophet Muhammad SAW during early period of Islam has been a source of inspiration. He was known as a religious figure and leader who deeply understood the importance of developing human resources. In the context of human resource management, implementation of management functions is the key to achieving effective human resource development. This research uses qualitative methods with literature study approach, documentation methods in collecting data, and content analysis in analyzing data. The research results show that in implementing the planning function, he implemented structured strategic planning, planned in stages, and made decisions based on criteria. In organizing implementation, he managed a multicultural work team wisely, placed human resources according to their qualifications, and demonstrated flexibility in decision making. In actuating implementation is carried out by building a loving environment and motivating friends through spiritual incentives. Implementation of supervision is carried out by monitoring compliance with rules, a human approach in supervision, wise response to violations, and being a role model in enforcing norms and rules. This research provides valuable insights into the management implemented by Prophet Muhammad SAW that can be adopted in human resource development in a modern context to achieve effective and sustainable goals. Keywords: Management Functions, Human Resource Management